2007
DOI: 10.1111/j.1547-5069.2007.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Self‐Reported Physical Activity Among Jordanian Adults

Abstract: Counseling these adults for physical activity should include application of behavior change strategies suitable to age and focused on increasing self-efficacy, decreasing barriers, increasing perception of benefits, and decreasing sedentary activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
26
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 25 publications
8
26
2
2
Order By: Relevance
“…Baseline difference between the two groups may also affected by recruiting more men in the control group. This finding is consistent with previous studies that reported higher level of physical activity among men in comparison with women [42][43][44].…”
Section: The Effect Of Intervention On Adoption Of a Heart Healthy LIsupporting
confidence: 96%
See 1 more Smart Citation
“…Baseline difference between the two groups may also affected by recruiting more men in the control group. This finding is consistent with previous studies that reported higher level of physical activity among men in comparison with women [42][43][44].…”
Section: The Effect Of Intervention On Adoption Of a Heart Healthy LIsupporting
confidence: 96%
“…However, women expressed stronger feelings of health responsibility. This finding confirms previous studies [42,43,49] that also reported higher health responsibility in women than in men. However, in the Jordanian culture, where women are the primary care providers for their families, women may consider themselves more responsible for the health and wellness of themselves as well as their families.…”
Section: Differences Between Men and Womensupporting
confidence: 95%
“…Deve-se considerar que, apesar de a prevalência ainda ser baixa, algum aconselhamento sobre atividade física chega aos mais pobres, o que pode se traduzir em mudança de comportamento no sentido de um estilo de vida mais saudável nesta população 20,21 , mesmo assumindo-se que é um grande desafio promover mudanças de comportamento neste grupo populacional 22 .…”
Section: Discussionunclassified
“…Evidence from many scientific studies shows that reducing this risk factor decreases the chance of having a heart disease or experiencing another cardiac event. Regular exercise has a favourable effect on many of the established risk factors for heart disease [4]. Eshah [5] has argued that the low levels of physical activity could be related to the Jordanians' perceptions of physical activity as not being part of the daily routine.…”
mentioning
confidence: 99%
“…Eshah [5] has argued that the low levels of physical activity could be related to the Jordanians' perceptions of physical activity as not being part of the daily routine. Ammouri et al [4] assessed the levels of physical activity of Jordanian adults aged 18 -75 years (n = 285) across three cities in Jordan. The study revealed that the male participants reported more physical activity than the females (P < 0.05).…”
mentioning
confidence: 99%